The Moderating Role of Managerial Skills on the Relationship between Monitoring and Evaluation Practices and Project Success in Teachers’ Colleges in Tanzania - Bugendi Joseph; William A. Pallangyo; Saganga Kapaya (An Overview of Literature, Language and Education Research Vol. 5, 2024)
The article assessed the moderation role of Managerial skills on the relationship between M&E practices and project success in teachers’ colleges in Tanzania. Structural Equation Modelling (SEM) was applied in testing the hypothesis. H0= Managerial skills significantly moderate the relationship between M&E and project success. The article adopted descriptive, cross-sectional and correlational survey design within the framework of a mixed method approach. The census technique was applied to include all public teachers’ colleges and College Management Team (CMT) members in the study. Ministerial education officials were involved in the study as key informants. Inferential analysis results revealed the existence of a direct positive and statistically significant influence of both M&E practices and managerial skills on project success (\(β\)= 0.579, P<0.001) and (\(β\)=0.268, P<0.001) respectively. Interaction between managerial skills and M&E practices through the interaction term (MSK*M&E) resulted in a negative (\(β\)=-0.169) but statistically significant (P<0.001) relationship between M&E and project success. Hence, it was concluded that CMTs did not possess adequate and appropriate managerial skills to support them in conducting M&E that influences teachers’ college project performance. It was further established that the low managerial skills among CMTs were caused by the criteria used for their appointment which was mainly inclined more on their teaching experience than managerial qualifications. Therefore, the article recommended that teachers’ colleges should strive to strengthen managerial skills among CMTs so as to enhance their ability to conduct M&E and management of teachers’ college projects as a whole.